EKSPLORASI FENOMENA LUMPUR LAPINDO DALAM PERSPEKTIF DARK TOURISM - Sukma Anindyah; Joko Mijiarto (Journal Publicuho, 2025)
This study aims to analyse the dark tourism spectrum of the Lapindo mudflow area as a dark tourism destination in Sidoarjo Regency, while contributing to academic literacy in tourism studies in Indonesia. The literature review refers to tourism theory, the concept of dark tourism, the dark tourism spectrum, and the Seven Dark Suppliers framework. This research employs a qualitative approach, utilising in-depth interviews and field observations. The findings reveal two main attractions, namely the Lapindo Tragedy Monument, which falls into the darker category, and the active mudflow site, which is classified as darkest within the dark tourism spectrum. Overall, the area’s potential is categorised as moderate, with its main strengths lying in its historical narrative and unique location, yet still requiring the development of facilities, interpretation, and tourism product diversification to ensure destination sustainability.